1987
DOI: 10.1037/0096-1523.13.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic form and scaling: Further investigations on the visual perception of lifted weight.

Abstract: Observers are able to judge accurately the weight hfted by another person when only the motions of reflectwe patches attached to the hfter's major hmb jomts and head can be seen (Runeson & Frykholm, 1981) What properttes of these complex kinematic patterns allow judgments of wetght to be made 9 The pattern of vanaUon m veloctty of the hfied object over posmon ~s explored as a source of mformat~on for wetght It ts found to provtde hmtted mformat~on How are variations m kmemaUc patterns scaled to allow judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
123
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 33 publications
(101 reference statements)
9
123
0
Order By: Relevance
“…Consistent with this proposal, a variety of studies have demonstrated that humans are surprisingly adept at acquiring useful information, such as object weight, from the observed visual kinematics of others' lifts (Bingham, 1987;Hamilton et al, 2007). Not only are individuals able to use these kinematic cues, but there is emerging evidence that the link between acting and perceiving is an automatic one.…”
Section: Introductionmentioning
confidence: 92%
“…Consistent with this proposal, a variety of studies have demonstrated that humans are surprisingly adept at acquiring useful information, such as object weight, from the observed visual kinematics of others' lifts (Bingham, 1987;Hamilton et al, 2007). Not only are individuals able to use these kinematic cues, but there is emerging evidence that the link between acting and perceiving is an automatic one.…”
Section: Introductionmentioning
confidence: 92%
“…Symmetrical peakening or flattening of trajectory forms are likewise potentially important. Bingham (1987) found that the flattening of an otherwise round harmonic form provided information to observers that the amount of weight being lifted by a person was near to the maximum liftable. Also, because asymmetry entails a change in the peakedness of a form, studying symmetrical peakening helps to differentiate the relative sensitivities to asymmetrical versus peakedness variations of trajectory forms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Runeson andFrykholm (1981, 1983) and Bingham (1987Bingham ( , 1993 demonstrated that the weight of objects lifted by others can be perceived solely via the kinematics of point-light displays. Those studies were conducted prior to the discovery of the inertial basis of heaviness perception; the researchers, therefore, were not in a position to make the conceptual links between inertia and kinematics proposed in the present research.…”
mentioning
confidence: 99%
“…Our approach was inspired by studies that have demonstrated that dynamical aspects of events, such as the relative mass of colliding objects (e.g., Flynn, 1994;Gilden & Proffitt, 1989;Runeson, 1977Runeson, /1983Todd & Warren, 1982) or the mass of lifted objects (e.g., Bingham, 1987Bingham, , 1993Runeson & Frykholm, 1981, 1983, can be perceived despite the fact that only motion (i.e., not forces) is visually accessible. The lawful relation between motion and dynamics inspired Runeson's kinematic specification of dynamics (KSD) principle.…”
mentioning
confidence: 99%